2020
DOI: 10.1002/joa3.12339
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Tpeak‐end, corrected Tpeak‐end, QT, and corrected QT intervals, Tpeak‐end/QT, Tpeak‐end/corrected QT ratios and heart rate variability according to decades in the healthy male subjects aged between 30 and 79 years

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractBackground: Heart rate variability (HRV) is a predictor of cardiac autonomic functions. Ventricular repolarization markers can indicate ventricular arrhythmias. We aimed to evaluate variations of HRV and these repolarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The authors concluded that as the age increases, basal Tp-e interval increases and HRV temporal parameters decrease significantly in the male subjects aged between 30 and 79 years, but HRV frequency parameters do not change. The relations between the markers from the repolarization group and heart rate variability seem complex and need further evaluation [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that as the age increases, basal Tp-e interval increases and HRV temporal parameters decrease significantly in the male subjects aged between 30 and 79 years, but HRV frequency parameters do not change. The relations between the markers from the repolarization group and heart rate variability seem complex and need further evaluation [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cardiac repolarization can traditionally be measured with QT interval, QT dispersion and corrected QT interval (QTc) from 12‐lead surface ECG. 3 , 4 , 5 On the other hands, frontal QRS‐T angle (fQRSTa) is a novel indicator of repolarization and depolarization heterogeneity. The relationship of the fQRSTa in many cardiovascular diseases has been investigated, and its importance in predicting cardiovascular arrhythmias has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac repolarization abnormalities are one of them. Cardiac repolarization can traditionally be measured with QT interval, QT dispersion and corrected QT interval (QTc) from 12‐lead surface ECG 3–5 . On the other hands, frontal QRS‐T angle (fQRSTa) is a novel indicator of repolarization and depolarization heterogeneity.…”
Section: Introductionmentioning
confidence: 99%